Praanggapan pada Teks Cerpen dalam Website ruangsastra.com Edisi Agustus 2025 (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to describe the forms and types of presuppositions found in two short stories published on the website ruangsastra.com, namely “Minum Teh Sebelum Mati” (“Drinking Tea Before Dying”) and “Pendongeng Keliling dan Tangisan Peluru” (“The Traveling Storyteller and the Cry of Bullets”). This research employs a descriptive qualitative method with an objective and pragmatic approach. Data were collected using the observation and note-taking method, then analyzed using distributional and referential analysis techniques. The results of the study show that a total of 32 presuppositions were identified and classified into six types, theory: existential, factive, structural, non-factive, lexical, and counterfactual presuppositions. Among these types, existential presuppositions were the most frequently found in the texts, while counterfactual presuppositions were the least common. These findings indicate that the use of presuppositions in short stories serves not only as a linguistic feature but also as an essential tool in constructing meaning and understanding narrative context. This research is expected to make a significant contribution to the development of pragmatic studies, particularly in the analysis of modern literary works, as well as to open new perspectives in understanding the interaction between language, meaning, and context in literary texts. The implications of this study may also serve as a foundation for further research on other pragmatic aspects in broader and more diverse literary works.